Esperando o superman : da diáspora do conceito e sua produção de diferenças e de resistências em escolas no Norte e Sul globais - Porto, João Luiz Simplício (2013)
Experiences in in Global North and Global South schools, inspired by Comparative Pedagogy and Phenomenology, having as main characters parents, students and teachers from North American and Brazilian schools are presented in this dissertation. The focus of this manuscript is on the diaspora, which occurs due to the scores attributed to these schools through the administration of standardized tests imposed to the students by the system of education. Because of this diaspora - a never-ending search for " category A", "better" or "richer" schools - one may point out the emergence of segregation, ethnic-racial stigmas, exclusion, and the maintenance of post-colonialism and the epistemicide of the North in relation to the South and also the implicit relationships between oppressor/oppressed. The North American Charter Schools, the standardized examinations from the states of Florida and Texas, as well as the "Prova Brasil" and its implications in Brazilian education are reported here. Besides the production of differences, the insurrections and resistances caused by the results of these tests, positive or negative, provided by national assessment instruments as well as by the Diaspora of Scores are also mentioned.